Signaling pathways mTOR and AKT in epilepsy (2016)
Introduction. The signaling pathway AKT/mTOR is a central axis in regulating cellular processes, particularly in neurological diseases. In the case of epilepsy, it has been observed alteration in the pathophysiological process of the same. However, they have not described all the mechanisms of these signaling pathways that could open the opportunity to new research and therapeutic strategies. Aim. To review existing partnerships between intracellular signaling pathways AKT and mTOR in the pathophysiology of epilepsy. Development. Epilepsy is a disease with a high epidemiological impact globally, so it is widely investigated regarding the pathophysiological components thereof. In that search they have been involved different intracellular signaling pathways in neurons, as determinants epileptogenic. Advances in this field have even allowed the successful implementation of new therapeutic strategies and to open the way to new research in the field. Conclusions. Improving knowledge about the pathophysiological role of the signaling pathway mTOR/AKT in epilepsy can raise new investigations regarding therapeutic alternatives. The use of mTOR inhibitors, has emerged in recent years as effective in treating this disease entity alternative however is clear the necessity of continue the research for new drug therapies. © 2016 Revista de Neurología.